Pengaruh Human Resources Management Practice terhadap Employee Intention to Stay pada PT Media Nusantara Informasi (Sindo) - Dina Sarah Syahreza; Andhika Ferdiansyah Harahap; Kania Humaira; Nathanael Nababan; Rizky Mardewina (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
This research aims to determine whether there is an influence of human resource management practices on employees' intentions to remain at PT Media Nusantara Information (Sindo). This research uses multiple linear regression analysis with a sample of 100 permanent employees of PT Media Nusantara Infomasi (Sindo). The independent variables in this research are Training and Development, Career Development, Compensation and Benefits, and Performance Assessment, while the dependent variable in this research is the employee's intention to stay. The results of this research show that Training and Development, Career Development, Compensation and Benefits, and Performance Appraisals have a positive and significant influence on employees' intention to stay. Furthermore, the research results show that the Compensation and Benefits dimensions have the strongest influence.